2013
DOI: 10.9790/2380-0447477
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Hematological and Serum Biochemical Parameters of Sahel Goats with Clinical Mastitis

Abstract: Mastitis is a widespread disease of the dairy goats associated with alterations in the physical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
3
0
0
Order By: Relevance
“…There was a significant decline in Haemoglobin, Total Erythrocyte Count, Packed Cell Volume, while elevated levels in Total Leucocyte count and Neutrophils with significant decrease in lymphocyte count and a non-significant reduction in eosinophils and monocyte value was observed in clinical mastitis affected goats as compared to healthy control (Table 4). These findings were in agreement with Abba et al (2013) [1] & Singh et al (2018) [22] who observed decreased Hb levels, leukocytosis, neutrophilia and lymphopenia in mastitis affected goats.…”
Section: Resultssupporting
confidence: 92%
“…There was a significant decline in Haemoglobin, Total Erythrocyte Count, Packed Cell Volume, while elevated levels in Total Leucocyte count and Neutrophils with significant decrease in lymphocyte count and a non-significant reduction in eosinophils and monocyte value was observed in clinical mastitis affected goats as compared to healthy control (Table 4). These findings were in agreement with Abba et al (2013) [1] & Singh et al (2018) [22] who observed decreased Hb levels, leukocytosis, neutrophilia and lymphopenia in mastitis affected goats.…”
Section: Resultssupporting
confidence: 92%
“…Disease-related stress and neutrophilia (subsequent leukocytosis) as well as lymphopenia may develop as a result of the endogenous production of corticosteroids in the mastitic group ( Duncan, 1994 ; Kaneko, 1997 ). Our finding was similar to that obtained in mastitis in goats ( Abba, 2013 ), in cattle ( Saleh et al ., 2022 ), and in camels ( Darwish, 2023 ).…”
Section: Discussionsupporting
confidence: 93%
“…Anorexia and renal dysfunctions may be acceptable causes for these deficiencies. Similar opinions were mentioned in mastitis in Sahel goats ( Abba, 2013 ) and in she camels ( Darwish, 2023 ).…”
Section: Discussionsupporting
confidence: 69%